Irradiation effects on electrical properties of DNA solution/Al Schottky diodes - Al-Ta'ii, Hassan Maktuff Jaber; Periasamy, Vengadesh; Iwamoto, Mitsumasa (Springer, 2018)
Deoxyribonucleic acid (DNA) has emerged as one of the most exciting organic material and as such extensively studied as a smart electronic material since the last few decades. DNA molecules have been reported to be utilized in the fabrication of small-scaled sensors and devices. In this current work, the effect of alpha radiation on the electrical properties of an Al/DNA/Al device using DNA solution was studied. It was observed that the carrier transport was governed by electrical interface properties at the Al–DNA interface. Current (I)–voltage (V) curves were analyzed by employing the interface limited Schottky current equations, i.e., conventional and Cheung and Cheung’s models. Schottky parameters such as ideality factor, barrier height and series resistance were also determined. The extracted barrier height of the Schottky contact before and after radiation was calculated as 0.7845, 0.7877, 0.7948 and 0.7874 eV for the non-radiated, 12, 24 and 36 mGy, respectively. Series resistance of the structure was found to decline with the increase in the irradiation, which was due to the increase in the free radical root effects in charge carriers in the DNA solution. Results pertaining to the electronic profiles obtained in this work may provide a better understanding for the development of precise and rapid radiation sensors using DNA solution.